Deradicalizing Interpretation of Jihad Verses by Sayyid Qutb - Deni Albar; Dadang Darmawan; Solehudin Solehudin (UIN Sunan Gunung Djati Bandung, 2023)
The research aims to explore and elaborate on the causes of radical and fundamentalist stigma in Sayyid Qutb, in interpreting the jihad verses in the Fi Zhilal Qur’an, which are considered the root cause of fundamentalist and radical and intolerant movements. The research method uses qualitative. The research subject is Sayyid Qutb's interpretation of the Fii Zhilal Al-Qur'an. The object of his research is the verses of jihad and qital verses scattered in the Qur’an. Data processing techniques through literature studies. The study results show that the stigma that is often leveled at Sayyid Qutb is a symbol of radicalism, intolerance, and anti-peace, even though in his work, he always gives a picture of peace, namely inner peace, household peace, and community peace. The emergence of radical movements, intolerance and inter-ethnic and religious conflicts in the world at the end of the 20th century allegedly originated from the Middle East, including; Qutb's thoughts in the interpretation of zhilal al-Quran, ma'alim fi at-tariq and several of his books. Meanwhile, Sayyid Qutb's wordview concept uses the term al-Tasawwur al-Islamy (Islamic Vision) or Sayyid Qutb's perspective on jihad verses. The deradicalization format of Sayyid Qutb's interpretation was written through his interpretation (Fi zhilalil Quran), the critical point is to illustrate that contemporary jihad is by working hard to preach preaching through speech and writing. The red line is that defensive jihad is put forward as a form of deradicalization.